Uzbekistan as Central Asian game changer? Uzbekistan's foreign policy construction in the post-Karimov era. Issue 2 (June 2019) - Dadabaev, Timur
With the death of first president of Uzbekistan Karimov, and Mirziyoyev's appointment as interim president in 2016 and election to the presidency in December of the same year, speculation appeared in the media suggesting that Uzbekistan would move closer to Russia because of the close personal ties between the president and Russian elites. Others suggested that Uzbekistan would either follow the path designed by the first president or fall into isolationism like Turkmenistan. This article aims to explain the continuity and shifts in Uzbekistan's foreign policy behaviour in the year following the death of the first president and the election of President Mirziyoyev.